Intersectional Design for an Accessible and Empowering World: Views from the 8th Forum of Design as a Process - Valentina Gianfrate; Lígia Lopes; Margherita Ascari; Simona Colitti (DIID, 2024)
Intersectionality is increasingly suggested as an innovative framework with the potential to advance the understanding and the action towards contrasting inequalities, by highlighting processes of stigmatisation and by encouraging a critical reflection to move beyond singular categories. The contribution explore the relation between the intersectional approach and design cultures and practices by presenting the main outcomes of Track 2 “Intersectional Design for an Accessible and Empowering World” in the frame of the 8th International Forum of Design as a Process. The contributions collected in this frame represent a wealth of practices, methods and applications that show how the theoretical contribution linked to the topic of intersectionality can be applied to the co-creation of innovation in design-driven practices in diversified geographies.